V Congresso da União Nacional
V Congresso da União Nacional. Augusto Cancela de Abreu (no uso da palavra), Albino dos Reis, Oliveira Salazar, Costa Leite (Lumbrales), Mário de Figueiredo e Gonçalves Rodrigues. 30 MAI. 1956.